2017
DOI: 10.1016/j.rboe.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor locally advanced around the knee: treatment and literature review

Abstract: Giant cell tumor (GCT) is a benign bone tumor with aggressive characteristics. They are more prevalent in the third decade of life and demonstrate a preference for locating in the epiphyseal region of long bones. They have a high local recurrence rate, which depends on the type of treatment and initial tumor presentation. The risk of lung metastases is around 3%.Between October 2010 and August 2014, nine patients diagnosed with locally advanced GCT or with pathological fracture to the knee level underwent surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…The principal of GCTs treatment should be based on completely removing the tumor, reducing recurrence, and preserving or recovering limb function [3,4,18]. In this study, clinical examination revealed no cases of lung metastasis or local GCT recurrence at the last follow-up.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The principal of GCTs treatment should be based on completely removing the tumor, reducing recurrence, and preserving or recovering limb function [3,4,18]. In this study, clinical examination revealed no cases of lung metastasis or local GCT recurrence at the last follow-up.…”
Section: Discussionmentioning
confidence: 56%
“…Currently, there are several methods that are used for the treatment of GCT around the knee, such as curettage or en-bloc resection with some reconstructive surgeries, arthrodesis by using a structural bone graft, a sandwich technique based on bone graft and polymethylmethacrylate (PMMA), and knee arthroplasty with structural bone allograft or knee prosthesis [3,4]. However, each of these methods has its advantages and disadvantages, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The giant cells play a main role in the expression of calcitonin receptors which has been reported recently, giant cells mainly consist of osteoclasts in chronic giant cell granulomas (CGCGs). This fact was confirmed with the help of immune-histochemical study in which osteoclast specific monoclonal antibodies were used [60]. GCTBs undergo secondary modifications including aneurysmal bone cyst (ABC) modification, foamy histiocytic combinations and responsive bone or osteoid production [61].…”
Section: Giant Cell Tumor Of Bone (Gctb)mentioning
confidence: 86%
“…Pathological fracture of distal femur giant cell tumor (GCT) frequently leads to joint surface defect, which is challenging to be repaired. Due to the eccentric growth of GCT [3], such joint destruction is often con ned in one condyle, but conventional methods needs to remove the both condyles together followed endoprosthesis replacement which will face lower prosthesis survival rate and multiple joint replacement [4][5][6], especially in relatively young patients. So, considering these lesions destroy a part of the articular surface, it makes sense to discuss partial repair of the articular surface.…”
Section: Introductionmentioning
confidence: 99%